2020
DOI: 10.3390/s20216020
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fetal Movement Simulator for the Performance Evaluation of Vibration Sensors for Wearable Fetal Movement Monitors

Abstract: Fetal movements (FM) are an important factor in the assessment of fetal health. However, there is currently no reliable way to monitor FM outside clinical environs. While extensive research has been carried out using accelerometer-based systems to monitor FM, the desired accuracy of detection is yet to be achieved. A major challenge has been the difficulty of testing and calibrating sensors at the pre-clinical stage. Little is known about fetal movement features, and clinical trials involving pregnant women ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The acoustic sensor and the piezoelectric diaphragm better determined the durations, intensities, and locations of kicks, than the accelerometer. Moreover, they demonstrated that the acoustic sensor and the piezoelectric diaphragm were able to detect weaker fetal movements, compared with the accelerometer [ 102 ].…”
Section: Sensing Devices In Healthcarementioning
confidence: 99%
“…The acoustic sensor and the piezoelectric diaphragm better determined the durations, intensities, and locations of kicks, than the accelerometer. Moreover, they demonstrated that the acoustic sensor and the piezoelectric diaphragm were able to detect weaker fetal movements, compared with the accelerometer [ 102 ].…”
Section: Sensing Devices In Healthcarementioning
confidence: 99%
“…The unique research paper with a novel system to assess the performance of sensors is reported in [ 30 ]. The study explores the development of a novel movement simulator devoted to assessing the performance of wearable systems for monitoring fetal movements.…”
mentioning
confidence: 99%